Pembaruan Data Profil Desa Gondang Kecamatan Gondang Kabupaten Mojokerto - Solehuddin, Solehuddin; Sumitro, Imam; Dwijayanti, Rizkya (CV. Ulil Albab Corp, 2024)
Village profile updates have strategic functions for development, planing, and utilization of village potential. This is the result of implementation on regional policy authentications that authorize the village to conduct the collaboration, planning, and management of the village independently in order to be optimal and maximized to the community or its citizens. Specific data about a village can be beneficial to determine what potential has opportunities to develop. In addition, specific data will cause facts about village infrastructure, village areas, and socioeconomic conditions and budata in each village. Therefore this article is prepared using qualitative method with descriptive type to be easily understood by the community. Results and discussions in this article indicate that the application of specific data collection as conducted by the village of Gondang can optimize the potential of the village, both in the exclusion, social cultural, and security of the village community supported by the Suprthive Village Institution.